2009
DOI: 10.1007/s00534-008-0039-5
|View full text |Cite
|
Sign up to set email alerts
|

Argon gas embolism in the application of laparoscopic microwave coagulation therapy

Abstract: After reviewing the cases, pneumoperitoneum (57.1%), hepatic needle punctures (42.8%) and direct application of the argon beam to the liver (28.6%) can be considered as risky processes in such events. Caution is necessary in the use of an argon beam in liver surgery to avoid life-threatening gas embolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…The use of ABC in MIS is first reported by Low et al [91] in 1993. Numerous studies describing the efficiency as well as the dangers of ABC have been well documented [9294]. …”
Section: Methodsmentioning
confidence: 99%
“…The use of ABC in MIS is first reported by Low et al [91] in 1993. Numerous studies describing the efficiency as well as the dangers of ABC have been well documented [9294]. …”
Section: Methodsmentioning
confidence: 99%
“…The argon beam coagulator is also known to have a risk to the gas emboli due to increased intraabdominal pressure under laparoscopic condition. Analysis of the literature and experienced surgeons propose its use respecting some rules: avoiding direct application close to the parenchymal surface, no pulverization on small hepatic veins holes, and venting the abdomen (open trocars) in order to decrease the intraperitoneal pressure [30]. Nowadays, PDE camera using ICG was reported that it is important to detect bile duct and intraoperatively [31, 32].…”
Section: Resultsmentioning
confidence: 99%
“…53 Use of the argon beam coagulator during laparoscopic procedures can produce alterations in the pneumopressure, and there have been a few reports of serious complications, including gas embolism and tension pneumothorax with this device. [54][55][56][57] Owing to these unfortunate incidents, there have been suggestions that the argon beam coagulator should only be used during laparoscopic surgery once all other possible methods of achieving hemostasis have been attempted. However, this technology has been shown to be safe as long as pressures are closely monitored and appropriate evacuations of flume and pressure is controlled.…”
Section: Use Of Sealants and Hemostats In Laparoscopic Liver Surgerymentioning
confidence: 99%